Prevalence of swallowing dysfunction screened in Swedish cohort of COPD patients - Gonzalez Lindh M; Blom Johansson M; Jennische M; Koyi H (International Journal of COPD, 2017)
Margareta Gonzalez Lindh,1,2 Monica Blom Johansson,1 Margareta Jennische,1 Hirsh Koyi2,3 1Department of Neuroscience, Speech and Language Pathology, Uppsala University, Uppsala, Sweden; 2Centre for Research and Development (CFUG), Uppsala University, County Council of Gävleborg, Gävle, Sweden; 3Department of Respiratory Medicine, Gävle Hospital, Gävle, Sweden Background: COPD is a common problem associated with morbidity and mortality. COPD may also affect the dynamics and coordination of functions such as swallowing. A misdirected swallow may, in turn, result in the bolus entering the airway. A growing body of evidence suggests that a subgroup of people with COPD is prone to oropharyngeal dysphagia. The aim of this study was to evaluate swallowing dysfunction in patients with stable COPD and to determine the relation between signs and symptoms of swallowing dysfunction and lung function (forced expiratory volume in 1 second percent predicted).Methods: Fifty-one patients with COPD in a stable phase participated in a questionnaire survey, swallowing tests, and spirometry. A post-bronchodilator ratio of the forced expiratory volume in 1 second/best of forced vital capacity and vital capacity <0.7 was used to define COPD. Swallowing function was assessed by a questionnaire and two swallowing tests (water and cookie swallow tests).Results: Sixty-five percent of the patients reported subjective signs and symptoms of swallowing dysfunction in the questionnaire and 49% showed measurable ones in the swallowing tests. For the combined subjective and objective findings, 78% had a coexisting swallowing dysfunction. No significant difference was found between male and female patients.Conclusion: Swallowing function is affected in COPD patients with moderate to severe airflow limitation, and the signs and symptoms of this swallowing dysfunction were subjective, objective, or both. Keywords: deglutition, deglutition disorders, swallowing, COPD, speech-language pathologist